Effect of Coagulant to Enhance Floatation Performance in Removing Organic and Grease - Hidayah, E. N.; A. Amalia; R. K. H. Putro; D. Putranto (Nusantara Science and Technology Proceedings)
Industrial wastewater treatment has been facing in high concentration of pollutant issues. One of the parameters issues is fat, oil, and grease (FOG) concentration. These parameters is needed to be considered since it will affect biological processes. Floatation is widely used processes in removing fat, oil, and grease in wastewater treatment processes. Recently, high concentration of oil, fat, and grease instead of suspended solid could decrease the performance of floatation. Therefore, it is necessary to enhance floatation performance. The objective of this research is to enhance floatation performance through coagulation by using various coagulant. Alum, FeCl3, and polyaluminium chloride (PAC) under various dosage was used as coagulant before flotation processes. The results shown that 20 mg/L PAC has high performance in removing FOG 230 mg/L into 20 mg/L or 91.3% FOG removal, and COD 1152 mg/L was treated into 230 mg/L or 80% COD removal.